Association between ear creases and peripheral arterial disease - Ramos, Paulo Mueller [UNESP]; Gumieiro, Juliana Hammoud [UNESP]; Miot, Hélio Amante [UNESP] (Universidade de São Paulo (USP), Hospital das Clínicas, 2010)
INTRODUCTION: Peripheral arterial disease is a severe manifestation of atherosclerosis that can lead to critical ischemia of the lower limbs and is also associated with high cardiovascular risk. Diagonal lobular and anterior tragal ear creases have been associated with coronary artery disease, but they have not yet been investigated in patients with peripheral arterial disease.OBJECTIVES: To evaluate the prevalence of ear creases among patients with peripheral arterial disease of the lower limbs, compared with patients without documented atherosclerotic disease.METHODS: Cross-sectional study including 60 male patients with peripheral arterial disease of the lower limbs and 60 dermatologic outpatients matched for age and gender. The associations were adjusted for other risk factors by conditional logistic regression.RESULTS: The prevalence of diagonal and anterior tragal ear creases was higher among cases (73% vs. 25% and 80% vs. 43%, respectively) than controls; these associations remained significant even when adjusting for other known risk factors of atherosclerosis (odds ratio = 8.1 and 4.1, respectively).CONCLUSIONS: Ear creases are independently associated with peripheral arterial disease and may be an external marker for risk identification.
Keywords: Ear; Atherosclerosis; Peripheral; Arterial; Disease